Hybrid Charging System Management With Automatic Switching Method - Abdillah Fashiha Ilman; Fitrah Maharani Humaira; Dzulkiflih Dzulkiflih; Imam Mawardi (Department of Electrical Engineering ITS and FORTEI, 2020)
Hybrid energy generation is a renewable energy power plant with more efficiency and advantages than a stand-alone generator. Using 2 generators for battery storage can speed up the charging of energy to the battery but in the battery charging system, there is still wasted energy and an uncontrolled Charging and Discharging system on the battery resulting in a short battery life. Therefore we need a tool to control the Charging and Discharging performance of the battery in order to optimize battery charging thereby extending battery life. Automatic Switching System is an innovation of Charging and Discharging activity management so that it does not occur simultaneously on the battery, this process is carried out by a microcontroller. The use of 2 DC power sources as a charging source helps speed up battery charging for 30 minutes faster than 1 source. Through several modes provided, this tool can select sources and batteries that can be used as a condition for Charging and Discharging.Keywords: automatic switching, hybrid, management system.